Effectiveness of visual instruction skit and sign language on oral health status among 5-18-year-old hearing-impaired children in South India: A cluster randomized clinical trial - Kondepudi, Vaishnavi; Kumar, R. V. S. Krishna; Srinivasulu, Gomasani; Prasanth, Punamalli Symon (Journal of the Indian Society of Pedodontics and Preventive Dentistry, 2024)
ABSTRACT Background: Literature on the effectiveness of theory-based oral health education on the oral hygiene status of hearing-impaired children is limited. Aim: To determine the effectiveness of a school oral health education intervention on oral hygiene status and oral health-related knowledge among 5-18-year-old children in Andhra Pradesh, India. Materials and Methods: A cluster randomized clinical trial was conducted among all institutionalized hearing-impaired children and young adults residing in various special care schools in Nellore district. Plaque Control record, gingival index (GI), and Decayed Missed Filled Teeth/ decayed extracted filled teeth and Decayed Missed Filled surfaces/ decayed extracted filled surfaces (DMFT/deft, and DMFS/defs) index were recorded; participants were selected and were randomly allocated to two groups using lottery method with 50 subjects in each group, Group I: sign language and Group II: video skit. Results: In all the age groups, preintervention DMFT and postintervention GI, DMFT, and DMFS were statistically significant in the sign language group and in the video skit group. Postintervention DMFS shows a significant difference. Conclusion: When compared with video instruction skit, sign language shows significant improvement in the oral hygiene status of CHI.